Knowledge, attitude, and skills of health and non health professionals treating paediatric obesity in Scotland. (24th May 2012) - Aboouf, S; Stewart, L; Rielly, JJ; Gillespie, J
Abstract : Background: Childhood obesity has risen up the political agenda in the UK, nonetheless evidence indicts poor skills and confidence in engaging with obese children and their families amongst professionals. Aim: The aim of the present study was to assess the Knowledge, Attitudes and Skills (KAS) of health and non-health professionals in two geographic areas in Scotland to evaluate the changes in KSA after one day training in paediatric obesity. Methods: A semi-quantitative questionnaire was distributed among participants pre and post training. Descriptive analysis of data was undertaken to quantify the self-reported changes in KAS pre and post training. Results: 42 participants (20 health and 22 non-health) completed both pre and post KAS questionnaires. The ability to diagnose obesity increased from 67.5% pre to 94.8% post training. The knowledge of childhood obesity guidelines increased from 27.5% to 82%. Self-confidence in treatment comprehension increased from 14% to 65.7%, while awareness of treatment goals increased from 30% to 80%. Confidence in the ability to discuss obesity issue with parents increased from 53.8% to 87.5%. Skills in the use of Body Mass Index (BMI) calculations and BMI charts increased from 21.9% and 29.2% to 40%. Conclusion: This present study highlighted alarming gaps in the KAS of health and non health professional participating in the engagement of obese children and their families. KAS improved after attending a specific tailored training course. This training course could be a step forward to accomplishing a higher standard health care for obese children.